The Unwed Father-Unworthy? The position of the natural father in South Africa following the Constitutional Court decision in Fraser v Children's Court Pretoria North - Bruk, Ilana (Department of Private Law, 2021)
Few topics in South African Family law have received as much attention by the Courts, Legislators, academics and the general public as the legal relationship between fathers and their extra-marital children. The widespread national interest peaked recently in 1997 in the delivery of the sensationalised Fraser judgement by the South African Constitutional Court. Through the declaration of this judgement, the Court broke new ground in pronouncing decisively not only on the rights of an unmarried father but also on the application of the right to equality within the context of a post-constitutional South Africa.